x2 -10x + 25 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\Leftrightarrow x\left(x+9\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-9\end{matrix}\right.\\ b,\Leftrightarrow\left(x+4-4\right)\left(x+4+4\right)=0\\ \Leftrightarrow x\left(x+8\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-8\end{matrix}\right.\\ c,\Leftrightarrow x\left(x-4\right)\left(x+4\right)=0\Leftrightarrow\left[{}\begin{matrix}x=0\\x=4\\x=-4\end{matrix}\right.\\ d,\Leftrightarrow\left(x-5\right)^2=0\Leftrightarrow x=5\)
a) \(\Leftrightarrow x\left(x+9\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=-9\end{matrix}\right.\)
b) \(\Leftrightarrow x\left(x+8\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=-8\end{matrix}\right.\)
c) \(\Leftrightarrow x\left(x-4\right)\left(x+4\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x=4\\x=-4\end{matrix}\right.\)
d) \(\Leftrightarrow\left(x-5\right)^2=0\\ \Leftrightarrow x=5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
`1,(4x^3+3x^3):x^3+(15x^2+6x):(-3x)=0`
`<=> 4 + 3 + (-5x) + (-2)=0`
`<=> -5x+5=0`
`<=>-5x=-5`
`<=>x=1`
`2,(25x^2-10x):5x +3(x-2)=4`
`<=> 5x - 2 + 3x-6=4`
`<=> 8x -8=4`
`<=> 8x=12`
`<=>x=12/8`
`<=>x=3/2`
`3,(3x+1)^2-(2x+1/2)^2=0`
`<=> [(3x+1)-(2x+1/2)][(3x+1)+(2x+1/2)]=0`
`<=>( 3x+1-2x-1/2)(3x+1+2x+1/2)=0`
`<=>( x+1/2) (5x+3/2)=0`
`@ TH1`
`x+1/2=0`
`<=>x=0-1/2`
`<=>x=-1/2`
` @TH2`
`5x+3/2=0`
`<=> 5x=-3/2`
`<=>x=-3/2 : 5`
`<=>x=-15/2`
`4, x^2+8x+16=0`
`<=>(x+4)^2=0`
`<=>x+4=0`
`<=>x=-4`
`5, 25-10x+x^2=0`
`<=> (5-x)^2=0`
`<=>5-x=0`
`<=>x=5`
![](https://rs.olm.vn/images/avt/0.png?1311)
1, \(x^2\) - \(x\) + \(\dfrac{1}{4}\) = 0
\(x^2\) - 2.\(x\).\(\dfrac{1}{2}\) + \(\dfrac{1}{4}\) = 0
(\(x\) - \(\dfrac{1}{2}\))2 = 0
\(x\) - \(\dfrac{1}{2}\) =0
\(x\) = \(\dfrac{1}{2}\)
2, \(x^2\) - 10\(x\) = -25
\(x^2\) - 10\(x\) + 25 = 0
(\(x\) - 5)2 = 0
\(x\) - 5 =0
\(x\) = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 3
a) x² + 10x + 25
= x² + 2.x.5 + 5²
= (x + 5)²
b) 8x - 16 - x²
= -(x² - 8x + 16)
= -(x² - 2.x.4 + 4²)
= -(x - 4)²
c) x³ + 3x² + 3x + 1
= x³ + 3.x².1 + 3.x.1² + 1³
= (x + 1)³
d) (x + y)² - 9x²
= (x + y)² - (3x)²
= (x + y - 3x)(x + y + 3x)
= (y - 2x)(4x + y)
e) (x + 5)² - (2x - 1)²
= (x + 5 - 2x + 1)(x + 5 + 2x - 1)
= (6 - x)(3x + 4)
Bài 4
a) x² - 9 = 0
x² = 9
x = 3 hoặc x = -3
b) (x - 4)² - 36 = 0
(x - 4 - 6)(x - 4 + 6) = 0
(x - 10)(x + 2) = 0
x - 10 = 0 hoặc x + 2 = 0
*) x - 10 = 0
x = 10
*) x + 2 = 0
x = -2
Vậy x = -2; x = 10
c) x² - 10x = -25
x² - 10x + 25 = 0
(x - 5)² = 0
x - 5 = 0
x = 5
d) x² + 5x + 6 = 0
x² + 2x + 3x + 6 = 0
(x² + 2x) + (3x + 6) = 0
x(x + 2) + 3(x + 2) = 0
(x + 2)(x + 3) = 0
x + 2 = 0 hoặc x + 3 = 0
*) x + 2 = 0
x = -2
*) x + 3 = 0
x = -3
Vậy x = -3; x = -2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^4-x^2+10x-25\)
\(=x^4-\left(x^2-10x+25\right)\)
\(=\left(x^2\right)^2-\left(x^2-2\cdot5\cdot x+5^2\right)\)
\(=\left(x^2\right)^2-\left(x-5\right)^2\)
\(=\left[x^2-\left(x-5\right)\right]\left[x^2+\left(x-5\right)\right]\)
\(=\left(x^2-x+5\right)\left(x^2+x-5\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)4x2+4x+1-x2-10x-25=0
`<=>(2x+1)^2-(x+5)^2=0`
`<=>(2x+1-x-5)(2x+1+x+5)=0`
`<=>(x-4)(3x+6)=0`
`<=>(x-4)(x+2)=0`
`<=>` \(\left[ \begin{array}{l}x=2\\x=-2\end{array} \right.\)
b)(x^2+x+7)(x^2+x-7)=(x2+x)2-7x
`<=>(x^2+x)^2-7^2=(x^2+x)^2-7x`
`<=>-7^2=-7x`
`<=>-49=-7x`
`<=>x=7`
Vậy x=7
![](https://rs.olm.vn/images/avt/0.png?1311)
Sửa đề: \(\dfrac{x+5}{x^2-5x}-\dfrac{x+25}{2x^2-50}=\dfrac{5-x}{2x^2+10x}\)
ĐKXĐ: \(x\notin\left\{0;5;-5\right\}\)
Ta có: \(\dfrac{x+5}{x^2-5x}-\dfrac{x+25}{2x^2-50}=\dfrac{5-x}{2x^2+10x}\)
\(\Leftrightarrow\dfrac{x+5}{x\left(x-5\right)}-\dfrac{x+25}{2\left(x^2-25\right)}=\dfrac{5-x}{2x\left(x+5\right)}\)
\(\Leftrightarrow\dfrac{2\left(x+5\right)^2}{2x\left(x-5\right)\left(x+5\right)}-\dfrac{x\left(x+25\right)}{2x\left(x-5\right)\left(x+5\right)}=\dfrac{-\left(x-5\right)^2}{2x\left(x+5\right)\left(x-5\right)}\)
Suy ra: \(2\left(x+5\right)^2-x\left(x+25\right)=-\left(x-5\right)^2\)
\(\Leftrightarrow2\left(x^2+10x+25\right)-x^2-25x=-\left(x^2-10x+25\right)\)
\(\Leftrightarrow2x^2+20x+50-x^2-25x=-x^2+10x-25\)
\(\Leftrightarrow x^2-5x+50+x^2-10x+25=0\)
\(\Leftrightarrow2x^2-15x+75=0\)
\(\Leftrightarrow2\left(x^2-\dfrac{15}{2}x+\dfrac{75}{2}\right)=0\)
\(\Leftrightarrow x^2-2\cdot x\cdot\dfrac{15}{4}+\dfrac{225}{16}+\dfrac{375}{16}=0\)
\(\Leftrightarrow\left(x-\dfrac{15}{4}\right)^2+\dfrac{375}{16}=0\)(vô lý)
Vậy: \(S=\varnothing\)
có phải câu hỏi là x2-10x+25=0 ko
Đề là x2-10x+25=0 hả
<=>(x-5)2=0
<=>x=5